The Dynamics Of Cultural Communication Through Acculturation In The Context Of Chinese-Dayak-Malay (Tidayu) Inter-Ethnic Marriage In Singkawang – Indonesia - Rizaldi Parani; Niyu Niyu; Desideria Lumongga Dwihadiah; Herman Purba (FAKULTAS DAKWAH UIN SALATIGA, 2025)
Singkawang, known as the “Hong Kong of Borneo,” is one of the most tolerant cities in Indonesia, where the Chinese ethnic group, with its distinctive cultural values, is the dominant cultural group in the city. With a population originating from diverse cultural backgrounds, interactions through inter-ethnic marriages, especially between Chinese, Dayak, and Malay ethnic groups, produce various dynamics of acculturation. This study aims to analyze the communication dynamics of cultural value acculturation in inter-ethnic marriages involving Chinese, Dayak, or Malay (Tidayu) ethnic groups in Singkawang. Using a phenomenological approach, this study explores the experiences of married Tidayu couples to understand how cultural differences are harmonized, shared identities are built, and family and social traditions are integrated. Data were obtained through interviews, observations, and literature review. The results of the study show that through inter-ethnic marriages Tidayu, Singkawang society has developed to be more inclusive by accepting each other. In the established dynamics of communication, it is important to maintain customs as part of efforts to adapt and acculturate culture. Communication dynamics cannot be separated from the worldview of the individuals involved. The results of this study are expected to have practical benefits in strengthening unity in the multicultural landscape of Singkawang, especially when facing the challenges of ethnic diversity.